IMPLEMENTATION OF THE ELECTRE METHOD IN DETERMINING THE DIRECTOR OF THE SUMATERA BLIND FOUNDATION - Marbun, Murni; Tumangger, Oktavia; Simalango, Arta Putri (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
A director is a position held by someone in an agency or institution. The head of an institution engaged in special education, namely the Extraordinary School, is responsible for managing the school, so many criteria must be met and selected. Determination of the director requires a method to be more efficient, and the results are more valid. This study aims to implement the ELECTRE method to elect administrators at blind education schools at the Sumatra Blind Education Foundation. The ELECTRE method can be used when alternatives that do not fit the criteria are removed and the appropriate alternative is selected. The criteria for being a director are having ability in visual impairment, ability as a leader, psychological test results, ability to speak English and the results of interviews with HBM Germany. Implementing the ELECTRE method provides a sequence of choices for each alternative; if the number of ecl = 1 is more significant, the alternative is better. The results showed that of the four alternatives as director candidates, alternative A1 was the better choice, while alternatives A2, A3 and A4 were eliminated.